Synthesis and Characterization of Hydroxyapatite from Green Mussel Shell with Sol-Gel Method - Charlena Charlena; Akhiruddin Maddu; Tatang Hidayat (Syarif Hidayatullah State Islamic University, 2022)
Hydroxyapatite (HAp) is a major component of bones and teeth. HAp is widely used to repair, fill, extend, and reconstruct damaged bone tissue. HAp is used for bone and dental implants, so it is necessary to synthesize HAp. HAp synthesis can utilize green mussel shell waste as a calcium precursor. This research synthesized HAp from a green mussel shell using the sol-gel method. The controlled synthesis parameter was pH, and the variable being compared was the heating temperature at 900 and 1100 °C. The HAp products were characterized by an X-ray diffractometer (XRD), Fourier-transform infrared spectrophotometer, and scanning electron microscope. The results showed that HAp was formed at alkaline pH, namely at pH 11. The XRD pattern showed that Hap was formed along with type A apatite carbonate, octacalcium phosphate, α- and β-tricalcium phosphate. The crystallinity was increased by raising the temperature and prolonging the heating time. The quality of HAp will improve with increasing crystallinity, and increasing the temperature will also raise the amount of HAp formed.